First molecular characterisation of Sarcocystis miescheriana in a pig carcass condemned during routine meat inspection in Poland - Korpysa-Dzirba Weronika; Rubiola Selene; Bilska-Zając Ewa; Różycki Mirosław; Chiesa Francesco; Bełcik Aneta; Samorek-Pieróg Małgorzata; Kubacki Jakub; Łukomska Anna; Karamon Jacek; Sroka Jacek; Cencek Tomasz (Journal of Veterinary Research)
This article presents the fourth detection of macroscopic cystic lesions due to sarcocystosis in domestic pigs during routine meat inspection worldwide, and the first molecular detection of Sarcocystis miescheriana in a domestic pig in Poland. Pigs can become intermediate hosts for S. miescheriana by accidental ingestion of oocysts or sporocysts present in food or water contaminated by the faeces of canids (definitive hosts).